The effect of Sc and Yb microalloying additions and aged-hardening heat treatment on corrosion behavior of Al-Mg alloys - Tuan, N. Q.
Sc-containing Al alloys are potentially applied in saline environment. However, the corrosion behavior and its mechanisms of Sc-containing Al alloys have not been paid much attention. In this research, the corrosion behavior of Al-4Mg, Al-4Mg-0.3Sc, and Al-4Mg-0.24Sc-0.06Yb alloys was investigated in 3.5wt% NaCl solution by immersion and potentiodynamic polarization analysis. Scanning electron microscope (SEM), transmission electron microscopy (TEM) and high-resolution TEM were used to characterize intermetallic phases and localized corrosion. The results showed that the Fe-containing intermetallic particles are cathodic with respect to the matrix and can lead to localized corrosion, whereas the high content of Mg makes the Fe-containing intermetallic particle less noble to the matrix. Yb-containing intermetallic particles did not show any dissolution of the matrix at the periphery of these particles. The results indicated that active dissolution and localized corrosion were the dominant corrosion mechanisms for Al-4Mg alloy. However the polarization curves of Al-4Mg-0.3Sc and Al-4Mg-0.24Sc-0.06Yb alloys showed spontaneous passivation followed by pitting corrosion. Results suggested that age-hardening heat treatment improved the stability of the passive film on Al-4Mg-0.3Sc and Al-4Mg-0.24Sc-0.06Yb alloys.